2020 Ieee Region 10 Conference (Tencon) 2020
DOI: 10.1109/tencon50793.2020.9293910
|View full text |Cite
|
Sign up to set email alerts
|

Power System Stability of Offshore Wind with an Energy Storage to Electrify O&G Platform

Abstract: The CapEx of offshore floating wind turbine generation (WTG) and battery energy storage system (BESS) have declined over the years which increases the cost feasibility of replacing gas turbine power generation in offshore oil and gas (O&G) platforms. This paper presents a study of an integrated system consisting of an offshore floating wind turbine generation (WTG) and O&G production platforms with battery energy storage system (BESS) onboard to meet the load demand. It is shown in cost analysis that the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4 where I q−ref and I q−Dev are generated from the frequency and voltage controllers. There is similarity in term of the design concept to integrate BESS to the droop control in micro grid which can be found in [12]. The other I d−ref and I q−ref are the signals of nominal power from PCC, which are added into current controller to assist in regulating optimal output power quality control to meet load demand.…”
Section: Design Of Energy Management Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…4 where I q−ref and I q−Dev are generated from the frequency and voltage controllers. There is similarity in term of the design concept to integrate BESS to the droop control in micro grid which can be found in [12]. The other I d−ref and I q−ref are the signals of nominal power from PCC, which are added into current controller to assist in regulating optimal output power quality control to meet load demand.…”
Section: Design Of Energy Management Systemmentioning
confidence: 99%
“…This is a critical element in transient stability improvement, which has always been the main research focus in the integration of OOR and WTG that is introduced in [10], [11]. Since then, a similar application has been presented in [12]. With an increase in capacity of BESS, the system can perform significantly better in transient stability.…”
Section: Introductionmentioning
confidence: 99%
“…Various concepts have been proposed to adapt to the new environmental restrictions such as including energy storage systems, hybrid power plants with DC power supply [1], [2] and integrating renewable energy. Different approaches have been proposed for the technical and/or economic sizing of energy storage [3]- [5] for offshore O&G installations that integrate wind power. However besides those concepts, achieving the environmental goals is also associated with the efficient use of the existing equipment and its impact on the platform's power quality (PQ), which is seldom addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown that integrating appropriately sized battery energy storage systems (BESS) to O&G applications can contribute to increased reliability [6], fuel efficiency improvements [7] and operating costs reduction [8]. In [9], the added value of energy storage in terms of enhancing frequency and voltage stability of a platform's power system, was reported, whereas in [10], [11] the particular technology of Li-ion batteries was proposed for reducing the transient load power deviation.…”
Section: Introductionmentioning
confidence: 99%